Contraindication of live vaccines in immunocompromised patients: an estimate of the number of affected people in the USA and the UK. (January 2017) - Varghese, L.; Curran, D.; Bunge, E.; Vroling, H.; van Kessel, F.; Guignard, A.; Casabona, G.; Olivieri, A.
Highlights: Live attenuated vaccines are usually contraindicated for individuals with immunocompromising (IC) conditions. An estimate of the size of the IC population is vital to make vaccine decisions. Key IC conditions were obtained from vaccination guidelines and recommendations. Approximately 3% of the total population of adults in the USA and UK had an IC condition.